Investigating the psychometric properties and confirmatory factor structure of the opinions about the gifted and their education as a teacher’s attitude scale - Shateri, Ainaz; Tahan, Mohammad; Azari, Farank (Frontiers in Psychology, 2025)
The present study aimed to determine the psychometric properties (PPs) and confirmatory factor structure of the Opinions about the Gifted and their Education (OGE) as a scale for measuring teacher’s attitudes via confirmatory factor analysis (CFA). The statistical population referenced in this research included elementary school teachers (n = 152), who were recruited from among the entire set of teachers working in the city of Ghaen, South Khorasan, Iran, during the 2023–2024 academic year; a multistage random sampling approach was employed. To assess the model’s adequacy, the chi-square (χ2) fit index, the χ2 to degree of freedom (df) ratio (χ2/df), the comparative fit index (CFI), the standardized root-mean-square residual (SRMR), and the relative fit index (RFI) were utilized. To establish the construct validity of the OGE scale, exploratory factor analysis (EFA) and CFA were then performed; these analyses revealed 10 factors that explained 60.12% of the common variance. Moreover, the results of the CFA demonstrated that the model exhibited an acceptable fit to the data. According to the Cronbach’s alpha coefficients, the given scale also exhibited good reliability.